Biochemical characterization of Bombyx mori α‐N‐acetylgalactosaminidase belonging to the glycoside hydrolase family 31. Issue 4 (31st March 2021) - Ikegaya, M.; Miyazaki, T.; Park, E. Y.
Abstract: Horizontal gene transfer is an important evolutionary mechanism not only for bacteria but also for eukaryotes. In the domestic silkworm Bombyx mori, a model species of lepidopteran insects, some enzymes are known to have been acquired by horizontal transfer; however, the enzymatic features of protein BmNag31, belonging to glycoside hydrolase family 31 (GH31) and whose gene was predicted to be transferred from Enterococcus sp. are unknown. In this study, we reveal that the transcription of BmNag31 increases significantly during the prepupal to pupal stage, and decreases in the adult stage. The full‐length BmNag31 and its truncated mutants were heterologously expressed in Escherichia coli and characterized. Its catalytic domain exhibits α‐ N ‐acetylgalactosaminidase activity and the carbohydrate‐binding module family 32 domain shows binding activity towards N ‐acetylgalactosamine, similar to the Enterococcus faecalis homolog, EfNag31A. Gel filtration chromatography and blue native polyacrylamide gel electrophoresis analyses indicate that BmNag31 forms a hexamer whereas EfNag31A is monomeric. These results provide insights into the function of lepidopteran GH31 α‐ N ‐acetylgalactosaminidase. Abstract : BmNag31, which encodes a glycoside hydrolase family 31 protein, is estimated to be transferred from Enterococcus sp. and the transcription level of BmNag31 increased during prepupal to pupal stage and decreased in the adult stage. BmNag31 showed α‐ N ‐acetylgalactosaminidase activity and the C‐terminal carbohydrate‐binding module bound N ‐acetylgalactosamine similarly to Enterococcus Nag31A. BmNag31 formed a hexamer in buffer solution whereas Enterococcus Nag31A is a monomer.